1983
DOI: 10.1152/ajpregu.1983.244.2.r249
|View full text |Cite
|
Sign up to set email alerts
|

Renal and adrenal responses to converting-enzyme inhibition in fetal and newborn life

Abstract: The renal and adrenal responses to a continuous infusion of the angiotensin-converting enzyme (ACE) inhibitor captopril were studied in 27 chronically catheterized sheep fetuses (less than 120 days gestation, n = 15, and greater than 130 days gestation, n = 12; term being 145 days) and in 12 newborn lambs between 8 and 21 days of age. Total renal blood flow did not change during ACE inhibition. However, the renal vascular resistance decreased significantly in newborn lambs (-21.8 +/- 5.7%) and in fetuses great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 35 publications
5
44
0
Order By: Relevance
“…However, the absence of significant changes in plasma A-I1 concentrations in the present study is against a role for the reninangiotensin system to influence changes in renal hemodynamics and renal function during the transition from fetal to newborn life. In this respect, the present findings confirm previous results suggesting that the renin-angiotensin system plays a minor role in controlling GFR in newborn animals (32,33).…”
Section: Bloodsupporting
confidence: 92%
“…However, the absence of significant changes in plasma A-I1 concentrations in the present study is against a role for the reninangiotensin system to influence changes in renal hemodynamics and renal function during the transition from fetal to newborn life. In this respect, the present findings confirm previous results suggesting that the renin-angiotensin system plays a minor role in controlling GFR in newborn animals (32,33).…”
Section: Bloodsupporting
confidence: 92%
“…The renin angiotensin system is highly activated at birth and during the maturation of renal hemodynamics (43-45). However, the contribution of angiotensin I1 as a vasoconstrictor in maintaining immature renal hemodynamics has not been demonstrated (14)(15)(16). The participation of vasodilators in the maturation of renal hemodynamics has received limited examination.…”
Section: 'mentioning
confidence: 99%
“…facilitates the matu---, rational increase in renal blood flow, remain largely unexplained. Previous investigations to explain the developmental phenomenon of renal hernodynamics have focused o n vasoconstrictor mechanisms such as an increased sympathoadrenergic response (8)(9)(10)(11)(12)(13), the highly activated renin angiotensin system (14)(15)(16), or activation of the prostanoid thromboxane ( 17). Prostaglandins, the only vasodilators examined, may participate in fetal renal hemodynamics (18) but have not been proven to regulate basal renal hemodynamics in the developing animal (1 5).…”
mentioning
confidence: 99%
“…However, it has been demonstrated that inhibition of kininase I1 using captopril does not modify urinary sodium and water excretion (34).…”
Section: Discussionmentioning
confidence: 99%